Assessment of an umbilical venous catheter dwell-time of 8–14 days versus 1–7 days in very low birth weight infacts (UVC – You Will See): a pilot single-center, randomized controlled trial. (April 2023) - Hess, Steffi; Poryo, Martin; Ruckes, Christian; Papan, Cihan; Ehrlich, Anne; Ebrahimi-Fakhari, Daniel; Bay, Johannes Saaradonna; Wagenpfeil, Stefan; Simon, Arne; Meyer, Sascha
Abstract: Background: Umbilical venous catheters (UVCs) are used for central vascular access in preterm infants, but controversy exits with regard to the optimum dwell-time. Patients and methods: Prospective, randomized controlled trial at a level III University neonatal intensive care unit (NICU), comparing a UVC dwell-time of 1–7 days (control group) to 8–14 days (intervention group) in very low birth weight (VLBW) infants. Primary outcome parameter: Number of infants requiring additional peripherally inserted central catheters (PICC) after removal of UVC. Secondary outcome parameters: Total number of central lines (CL = UVC and PICCs) until time point of full enteral feeds (130–160 mL/kg/d), total number of intravenous vascular catheters, number of CL-associated complications (infection, thrombosis/emboli, organ injury, secondary CL dislocation), number of X-rays for assessment of CL positioning, and days of therapy (DOT) (teicoplanin) for CL-associated blood stream infections (CLABSI). Results: Of 116 patients screened for eligibility, 63 patients were enrolled – control group: 31 infants, mean gestational age (GA) 28 0 weeks (standard deviation (SD) 2.6 weeks), mean birth weight (BW) 988.9 g (SD 322.0 g); intervention group: 32 infants, mean GA 28 5 weeks (SD 3.0 weeks), mean BW 1078.9 g (SD 324.6 g). In the control group, 28 infants required additional PICCs versus 16 in the intervention group (p < 0.001); total number of CLs: control group n = 58 versus intervention group n = 28; p < 0.001, and the total number of venous vascular devices was also significantly higher in the control group (109 versus 61; p = 0.04). No significant differences were seen with regard to CL-associated complications (p = 0.09). The number of X-rays for assessment of correct CL-position significantly lower in the intervention group (144 versus 96; p = 0.03). In the intervention group, length of hospital stay was significantly shorter (88.1 (SD: 35.3 days) versus 68.1 (SD: 32.6 days); p = 0.03) and GA significantly lower at discharge from the hospital (40 4 : SD: 3 3 weeks) versus 38 5 : SD: 2 5 weeks; p = 0.02. No differences existed with regard to neonatal morbidities and mortality at 36 weeks gestational age. Conclusions: A longer UVC dwell-time of up to 14 days significantly decreased the number of painful invasive vascular procedures and radiation exposure, and shortened the length of the hospital stay. The findings of our pilot study should be confirmed in a larger, multi-center RCT with the primary focus on catheter-associated complications. Highlights: Umbilical venous catheters (UVCs) and peripherally inserted central catheters (PICC) are commonly used to establish a secure central vascular route in preterm infants, but controversy exits with regard to the optimum dwell-time. The most significant clinical effects of early pain exposure may be on neurodevelopment, contributing to later attention, learning, and behavioral problems. A longer UVC dwell-time of 8-14 days versus 1-7 days significantly decreased the number of painful invasive vascular procedures and radiation exposure, and shortened the length of the hospital stay. Reducing the number of painful invasive procedures related to vascular access in very immature infants has the potential to positively impact on both long-term pain perception and important social competencies.